2011
DOI: 10.1016/j.bbi.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory footprints of alcohol-induced oxidative damage in neurovascular components

Abstract: Microvessels, the main components of the blood-brain barrier (BBB) are vulnerable to oxidative damage during alcohol-induced stress. Alcohol produces oxidative damage within the vessels and in the brain. Using our animal model of catheter implant into the common carotid artery (CCA), we trace the footprints of alcohol-induced oxidative damage and inflammatory process at the BBB and into the brain. The uniqueness of the finding is that ethanol causes oxidative damage in all neurovascular components by activatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
3
38
0
1
Order By: Relevance
“…Labeled cells were infused into the right common carotid artery (2 × 10 6 cells per rat) using 27.5 G needle (see Alikunju et al, (13), for the detailed protocol). Adhesion and infiltration of these cells were detected in intact brain microvessels under fluorescent microscope.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Labeled cells were infused into the right common carotid artery (2 × 10 6 cells per rat) using 27.5 G needle (see Alikunju et al, (13), for the detailed protocol). Adhesion and infiltration of these cells were detected in intact brain microvessels under fluorescent microscope.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that cerebral vascular integrity (the BBB) is very sensitive to oxidative stress during substance of abuse (11, 12). Ensuing oxidative damage of the BBB leads to neuroinflammation and neuronal degeneration (1315). Understanding of underlying molecular and biochemical mechanisms will help define the characteristic biomarkers of cerebral vascular injury and be able to formulate a preventive strategy to mitigate the adverse acute effects of blast exposure and related chronic neurological complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, alcohol oxidation by brain cytosolic catalase is a possible ROS-producing route, as is inducible cytochrome P4502E1 in endoplasmic reticulum ([29]. Also, alcohol-dependent microglial activation leading to increased brain NADPH oxidase activity and resultant ROS generation has been implicated in prolonged alcohol exposure [30]. However, the above alcohol-ROS generating possibilities have been examined largely in acute and chronic alcohol rodent models that utilize non-binge alcohol intake or administration (liquid diets, water, vapor chamber)—models that do not generally entail the repetitive, highly elevated blood alcohol levels and nadirs of binge administration/intoxication.…”
mentioning
confidence: 99%
“…Nevertheless, our data comprise the outcomes of all experimental groups in order to understand the overall associations between the expression of neuroinflammatory markers and NSS, not necessarily the effect of TBI/Alcohol alone on either of those markers. It is also important to know that this association does not indicate a causal relationship and other potential factors should be considered including acetaldehyde, the metabolic by-product of alcohol metabolism, as it is highly toxic and can activate enzymes such as NADPH oxidase and inducible nitric oxidase synthase, causing oxidative damages on neurovascular cells with subsequent neuroinflammation (Alikunju et al, 2011). Since there is no significant main effect of TBI on body weight gain when compared to sham controls, we conclude that mild TBI produced in our model does not affect subsequent feeding and nutrition.…”
Section: Discussionmentioning
confidence: 99%